DETERMINASI MINAT MASYARAKAT BERINVESTASI EMAS DENGAN PENDEKATAN SYARIAH BERDASARKAN PENGETAHUAN INVESTASI, PERSEPSI KEUNTUNGAN, PERSEPSI RISIKO, PERSEPSI INFLASI, DAN LITERASI KEUANGAN SYARIAH - Apriyanto, Suryadi; Busnetty, Ida (STKIP Persada Khatulistiwa Sintang, 2026)
Gold investment is a form of wealth management that is permitted and even recommended in Islamic law, as gold is considered mal with stable intrinsic value and the ability to preserve wealth against the risk of inflation. This study aims to analyze the partial and simultaneous effects of investment knowledge, perceived benefits, perceived risk, perceived inflation, and islamic financial literacy on the public’s interest in gold investment. The analytical method used is primary data described from quantitative data obtained through offline and online questionnaire distribution. This study employs a quantitative research approach with purposive sampling. Based on the predetermined criteria, 300 respondents were obtained, and data analysis was conducted using SmartPLS 3.0 software. The results indicate that Perceived Benefits, Perceived Inflation, and Islamic Financial Literacy have a positive and significant effect on Interest in Gold Investment. In contrast, Perceived Risk has a negative and significant effect, while Investment Knowledge does not show a significant effect. Simultaneously, all independent variables have a strong influence on Interest in Gold Investment.